The seventh champion - Mercedes, Sylvia (Mercedes, Sylvia. Dragon Queen duology., 2025)
"A dragon princess joins forces with a scarred prince to escape a competition for her hand in marriage, unaware he is hiding dark secrets of his own in the first of a new romantasy duology from the author of Bride of the Shadow King. Swept from her quiet life as an apothecary's apprentice to the treacherous court of the High King, Rosie Harpwood is shocked to discover she is the long-lost daughter of the demonic Dragon Queen. Reawakening her dormant magic is the kingdom's only hope for salvation, but the journey is perilous, and she'll need a champion to guide her. So the High King hosts a series of trials to determine which prince is worthy of the honor - as well as claiming Rosie's hand in marriage. A talented healer and lover of small, fluffy creatures, Rosie wants nothing to do with demon queens or saving the world. Determined to escape this fate, she joins forces with one of the champions to plot her getaway. Prince Valtar may be enigmatic and a little bit terrifying, but something about him makes her blood burn in ways that have nothing to do with her dragon heritage. Trained from youth to serve the Dragon Queen, Valtar has proven himself a ruthless assassin. Posing as a suitor to get close enough to his target shouldn't be a problem. But Valtar wasn't planning on his target being Rosie, the girl he failed to assassinate years ago . . . who has haunted his dreams ever since"-- Provided by publisher.